Farming based on flood-spreading weirs reduced land degradation and significantly increased diversified crop and fodder production in three agro-pastoral communities in Afar, Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
Harnessing flash floods emerging from neighboring highlands helped convert degraded dry rangelands in Afar Region, Ethiopia into productive land supporting diversified crop and fodder production. The integrated solutions increased vegetation cover from 13% to 29% of the area, reduced degraded rangelands from 87% to just 28%, improved land quality (soil moisture and nutrients), and enabled a change in land allocation from communal use to individual occupation. Some 198 agropastoral households in three sites have directly benefitted so far.